POSISI DAYA SAING DAN TINGKAT KONSENTRASI PASAR EKSPOR KARET ALAM INDONESIA DI PASAR GLOBAL - Lindung, Lindung; Jamil, Ahmad Syariful (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2018)
Most domestic natural rubber production is exported. The aim of this study is to analyze the position and competitiveness of natural rubber as an Indonesia’s main export commodity. This research used time series data of natural rubber export from 2001 until 2016 from Thailand, Indonesia, Malaysia and Vietnam. The rubber market structure was oligopoly. In addition, Indonesia has both comparative and competitive advantages based on RCA and ECI index. Differentiation of natural rubber is one of alternative ways that can be taken Indonesia